2021
DOI: 10.1186/s13244-021-01131-1
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural fasting for contrast-enhanced CT: when experience meets evidence

Abstract: Traditional preparatory fasting policy prior to iodinated contrast media (ICM) assisted contrast-enhanced CT (CECT) examinations lacks methodologically acceptable evidence. Considering the possible negative effects of preprocedural fasting, the latest European Society of Urogenital Radiology guidelines V10.0 and American Committee of Radiology 2021 guidelines clearly state that preprocedural fasting is not recommended prior to routine intravenous ICM administration. This comprehensive and detailed Review prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Therefore, fasting protocols for pediatric cardiovascular CT may differ among institutions. Notably, excessive fasting is not recommended, particularly in infants and young children, because of the detrimental effects of dehydration and hypoglycemia 43 …”
Section: When To Perform Cardiac Ct In Children: Clinical Indicationsmentioning
confidence: 99%
“…Therefore, fasting protocols for pediatric cardiovascular CT may differ among institutions. Notably, excessive fasting is not recommended, particularly in infants and young children, because of the detrimental effects of dehydration and hypoglycemia 43 …”
Section: When To Perform Cardiac Ct In Children: Clinical Indicationsmentioning
confidence: 99%
“…As a time-honored tradition, preprocedural fasting for 4–6 h is typically required prior to contrast-enhanced CT (CECT) in most medical institutions worldwide, to reduce the possibility of adverse consequences (e.g., emetic complications and aspiration) after injection of iodinated contrast media (ICM) [ 1 3 ]. Although this policy lacks methodologically acceptable evidence, and the fasting time durations and contents vary considerably in different medical institutions, preprocedural fasting is still a fairly common request worldwide [ 3 ]. Nowadays, with the extensive applications of non-ionic ICM, the incidence of emetic complications has reduced to an extremely low level (nausea 0.013%, vomiting 0.059%) [ 4 ], which is much lower than that reported by Katayama et al about 30 years ago [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with the extensive applications of non-ionic ICM, the incidence of emetic complications has reduced to an extremely low level (nausea 0.013%, vomiting 0.059%) [ 4 ], which is much lower than that reported by Katayama et al about 30 years ago [ 5 ]. According to our rigorous and extensive literature review [ 3 ], no aspiration pneumonia has been reported due to the lenient implementation of preparatory fasting. Non-fasting would not increase the risk of aspiration pneumonia and the incidence of emetic complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations